PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PAI KELAS XII MIPA DI SEKOLAH MADRASAH ALIYAH KOTA PAREPARE - Sulfikar Muhaemin (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2022)
This study aims to determine the effect of using audio visual media on the achievement of student learning outcomes in Islamic religious education subjects for class XII MIPA at Madrasah Aliyah School in Parepare City. This type of research is Ex-post facto quantitative research. The research sample used random sampling, namely 45 samples of students of class XII MIPA Madrasah Aliyah Negeri 1 Parepare City. Data collection techniques using observation techniques, questionnaires using SPSS software version 2.4. Based on the results of the analysis on the effect of using audio-visual media and student learning outcomes, the data value of person corelattion is 0.921 or 92.10% at the relationship level of 0.80–1,000. It is known that the f value is 232.64 with a significant level of 0.02 0.05 . it can be explained that Ha is accepted and Ho is rejected, meaning the effect of using audio-visual media on student learning outcomes in Islamic Religious Education Class XII MIPA at Madrasah Aliyah Negeri 1 Parepare City. While the value of SE = 0.831 or 8.31.% which means that the effective contribution (SE) of audio-visual media (X) to students' learning motivation (Y) is 8.31%.